2001
DOI: 10.1002/1521-3773(20010601)40:11<2004::aid-anie2004>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Click Chemistry: Diverse Chemical Function from a Few Good Reactions

Abstract: Beyond the Paradigm of Carbonyl ChemistryLife on Earth requires the construction of carbon ± carbon bonds in an aqueous environment. Carbonyl (aldol) chemistry is natures primary engine of CÀC bond formation. Not only do the requisite carbon electrophiles (carbonyls) and nucleophiles coexist in water, but water provides the perfect environment for proton shuttling among reactants, which is required for reversible carbonyl chemistry.With CO 2 as the carbon source and a few good carbonyl chemistry based reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
4,035
2
38

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 12,228 publications
(4,098 citation statements)
references
References 162 publications
23
4,035
2
38
Order By: Relevance
“…'Click chemistry' is a term first coined by Sharpless and co-workers 65,66 to describe modular, high-yielding reactions which are ideally insensitive to the presence of oxygen and water. The azide-alkyne 1,3-dipolar cycloaddition (or the 1,3-Huisgen reaction 67 ) was identified as the 'cream of the crop' of 'click' reactions.…”
Section: Terdentate Ligandsmentioning
confidence: 99%
“…'Click chemistry' is a term first coined by Sharpless and co-workers 65,66 to describe modular, high-yielding reactions which are ideally insensitive to the presence of oxygen and water. The azide-alkyne 1,3-dipolar cycloaddition (or the 1,3-Huisgen reaction 67 ) was identified as the 'cream of the crop' of 'click' reactions.…”
Section: Terdentate Ligandsmentioning
confidence: 99%
“…25 The requirements of a Clickreaction are: (1) robust and quantitative, i.e., the reactions are highly selective and the yields are near 100%: (2) the reactions are able to proceed in the presence of a variety of solvents such as water, organic solvents, etc., irrespective of their protic/ aprotic or polar/non-polar character: (3) high tolerance to other functional groups and (4) the reaction proceeds at various types of interfaces such as solid/liquid, liquid/liquid or even solid/solid. 26 Another advantage of these reactions is the requirement of only stoichiometric amounts of starting materials with virtually no by-products being formed, which greatly simplifies the purification procedures.…”
Section: Dendronized Polymersmentioning
confidence: 99%
“…We chose to test its catalytic activity in the [3+2] cycloaddition of azides and alkynes. 24 The reaction of heptyl azide with phenyl acetylene, under mild conditions (room temperature, solvent-free), using a low catalyst loading was investigated. Comparison with [Cu(Cl)(SIMes)] [SIMes = (N,N'-bis-[2,4,6-(trimethyl)phenyl]imidazolidin-2-ylidene], which represents the state-of-the-art 25 for such a reaction, showed that the cyclopropenylidene complex 2 has a higher catalytic activity than its NHC analogue.…”
mentioning
confidence: 99%